h.hofstede (h.hofstede@hogeland.nl)

       
1. 2(x + 4) - 5x = 11
2x + 8 - 5x = 11
-3x + 8 = 11
-3x = 3
x = -1
   
       
2. 3 - (2x + 5) = 12
3 - 2x - 5 = 12
-2 - 2x = 12
-2x = 14
x = -7
   
       
3. 4 + 4(x - 2) = 3 - (x + 5)
4 + 4x - 8 = 3 - x - 5
-4 + 4x = -2 - x
4x = 2 - x
5x = 2
x = 2/5
   
       
4. 5x - (2x - 6) = 3(6 - 4x)
5x - 2x + 6 = 18 - 12x
3x + 6 = 18 - 12x
3x = 12 - 12x
15x = 12
x = 12/15 = 4/5
   
       
5. 2(2x - 3) + 3(4 - 5x) = x + 7
4x - 6 + 12 - 15x = x + 7
6 - 11x = x + 7
-11x = x + 1
-12x = 1
x = -1/12
   
       
6. 7 - 3(x - 3) = 8x
7 - 3x + 9 = 8x
16 - 3x = 8x
16 = 11x
x
= 16/11 
   
       
7. x - 2(5 + 2x) = -2(8x - 3)
x - 10 - 4x = -16x + 6
-3x - 10 = -16x + 6
-3x = -16x + 16
13x = 16
x = 16/13
   
       
8. -6(3x - 2) = 2 - (x - 5)
-18x + 12 = 2 - x + 5
-18x + 12 = 7 - x
-18x = -5 - x
-17x = - 5
x = 5/17
   
       
9. 3 + 3(2 + x - 5) = -5(6x + 7)
3 + 6 + 3x - 15 = -30x - 35
-6 + 3x = -30x - 35
3x = -30x - 29
33x = -29
x = -29/33
   
       
10. -6(5x + 3) = -8(2x + 7)
-30x - 18 = -16x - 56
-30x = -16x - 38
-14x = -38
x = 38/14 = 19/7
   
       
11. 4(5 - 2x) = 8x + (x - 4) - 5
20 - 8x = 8x + x - 4 - 5
20 - 8x = 9x - 9
-8x = 9x - 29
-17x = -29
x = 29/17
   
       
12. 3x - 7(x - 5) = 12
3x - 7x + 35 = 12
-4x + 35 = 12
-4x = -23
x = 23/4
   
       
13. 7(2 - 13x) = 8 - 16x
14 - 91x = 8 - 16x
-91x = -6 - 16x
-75x = -6
x = 6/75  = 2/25
   
       
14. 12(x - 6) = -3(2x - 7)
12x - 72 = -6x + 21
12x = -6x + 93
18x = 93
x = 93/18 = 31/6
   
       
15. 9x - 2 - 3(6 - 4x) =  4 + 5x
9x - 2 - 18 + 12x = 4 + 5x
21x - 20 = 4 + 5x
21x = 24 + 5x
16x = 24
x = 24/16 = 3/2
   
       
16. 6 - (x - 5) = -2x
6 - x + 5 = -2x
11 - x  = -2x
11 = -x
x
= -11
   
       
17. 10 + 4(3 - 3x) = 10 - 2(8 - x)
10 + 12 - 12x = 10 - 16 + 2x
22 - 12x = -6 + 2x
-12x = -28 + 2x
-14x = -18
x = 2
   
       
18. 5x - 3x - (3 + 9x) = -2(x - 5)
5x - 3x - 3 - 9x = -2x + 10
-7x - 3 = -2x + 10
-7x = -2x + 13
-5x = 13
x = 13/5
   
       
19. 4 - (-5x - 4) = -2x- 7
4 + 5x + 4 = -2x - 7
8 + 5x = -2x - 7
5x = -2x - 15
7x = -15
x = -15/7
   
       
20. 3x + 2(14 - 5x) = -2x - (5 - 6x)
3x + 28 - 10x = -2x - 5 + 6x
-7x + 28 = 4x - 5
-7x = 4x - 33
-11x = -33
x = 3
   
       

h.hofstede (h.hofstede@hogeland.nl)